Food preferences of fish in integrated multi-trophic aquaculture freshwater ponds based on fatty acids and stable isotopes - Nahon Sarah; Jaeger Christophe; Menniti Christophe; Roucaute Marc; Kerhervé Philippe; Mortillaro Jean-Michel; Aubin Joël (Aquatic Living Resources)
Integrated multi-trophic aquaculture (IMTA) is a solution to biomitigate waste by rearing species from different trophic levels. In European freshwater fishponds, common carp is often produced along with secondary fish species. Developing recycling IMTA systems requires better understanding of the complexity of trophic interactions between fish. Analyses of fatty acid and stable isotopes of carbon and nitrogen are suitable tools for determining food preferences of fish species. Three IMTA systems, including carp, roach, rudd and perch, were investigated in ponds: a semi-intensive (SI) pond in which fish were fed pellets; a semi-intensive pond in which fish were fed pellets, coupled with a lagoon planted with macrophytes (SIC); and an extensive (E) pond in which fish were not fed pellets. In the SI and SIC ponds, fatty acid profiles of carp, roach and rudd were closed to those of pellets. The δ13C and δ15N values of fish confirmed that they mainly fed on pellets, but the diet of roach and rudd also contained natural food sources. In the E ponds, fatty acid profiles of carp, roach and rudd slightly differed but their δ13C and δ15N values were similar. Mixing model indicated that fish from E ponds mainly fed on zooplankton. Regardless of the IMTA systems, fatty acid and stable isotope analyses indicated that juveniles consumed mainly large zooplankton. In the three systems, the FA profile of perch was closed to that of juvenile fish. Mixing model estimated that perch supplemented their diet with large zooplankton and crayfish. In the SI and SIC ponds, the distribution of commercial pellets drove the trophic interactions among fish. In the E ponds, fish had significant feeding overlap due to the limited resources available.